Synthesis of Tert-Octylsalicylaldoxime and Its Application in Extraction of Cu(II) - Li, Liqing; Feng, Luo; Liao, Chunfa; Li, Fangxu; Yang, Liqin (Frontiers in Chemistry, 2021)
The alkyl salicylaldoxime has attracted more and more attentions recently due to the complex branched alkyl groups. In this study, a novel alkyl salicylaldoxime, tert-octylsalicylaldoxime, was successfully synthesized by one-pot method. The yield and purity by elemental analysis were 96.17% and 94.13%, respectively. The structure was confirmed by elemental analysis, FT-IR, 1H NMR (Nuclear Magnetic Resonance), 13C NMR spectroscopy and MS. Results showed that tert-octylsalicylaldoxime with new structure exhibited excellent extraction ability and selectivity for Cu(II), and can be successfully used to recover Cu from copper-nickel alloy electroplating wastewater. Thus, this product has the potential to be used as a powerful copper extractant in future.